Incarceration status at buprenorphine initiation and OUD treatment outcomes during pregnancy - Nguyen, Andrea; Shadowen, Hannah; Shadowen, Caroline; Thakkar, Bhushan; Knittel, Andrea K.; Martin, Caitlin E. (Frontiers in Psychiatry, 2023)
Introduction Opioid use disorder (OUD) is a leading cause of pregnancy-associated deaths. OUD treatment with buprenorphine (BUP) reduces overdose risk and improves perinatal outcomes. Incarceration can be a barrier to receipt of OUD treatment during pregnancy and postpartum. The objective of this study was to examine differences in BUP continuation at delivery by patients’ incarceration status at the time of BUP initiation. Methods This is a secondary analysis of a retrospective cohort study of pregnant patients with OUD who delivered at an academic medical center and initiated BUP between January 1, 2018, and March 30, 2020. The primary outcome was BUP continuation at delivery, abstracted from the state prescription monitoring program and electronic medical record, along with incarceration status. Bivariate analysis was used to assess the relationship between BUP continuation and incarceration status. Results Our sample included 76 patients, with 62% of patients incarcerated at BUP initiation (n = 47). Among the entire sample, 90.7% (n = 68) received BUP at delivery. Among patients who were incarcerated at BUP initiation, 97% remained on BUP at delivery; among patients who were not incarcerated at BUP initiation, 79% remained on BUP at delivery (p = 0.02). Conclusion In our sample from a health system housing a care model for pregnant and parenting people with OUD with local jail outreach, BUP continuation rates at delivery were high, both for patients who were and were not incarcerated at BUP initiation. Findings are intended to inform future work to develop and evaluate evidence-based, patient-centered interventions to expand OUD treatment access for incarcerated communities.